Psychospołeczna perspektywa adaptacji szkolnej dzieci – konceptualizacja zjawiska - Renata Michalak (Problemy Wczesnej Edukacji)
Regardless of the theoretical perspective, the school adaptation is treated in an instrumental way and identifies with the concept of adaptation, adjustment, fitness, and is considered as the basic problem of the student’s educational functioning. However, it should be clearly emphasized that compliance included in the school adaptation does not mean passive adaptation, submission to external influences, because it does not exclude the possibility of student’s innovative, creative role and active participation in the institution’s life. The article attempts to show school adaptation of children as an extremely important aspect of human adaptation, understood as the whole-life process of building balance and striving to maintain it between constantly changing and mutually conditioning entities: the human body and the its life environment. This process takes place with different dynamics de-pending on each episode of life, and more importantly, with a different value for its further course. Therefore, the quality of school adaptation experiences taken out of childhood exerts significant impact on the course of further human functioning.